Community-Based Water Management: An Institutional Study In PAMDes Sumberagung, Bantul, DIY - Rahmah Risqi Widhiyastuti; Akhmad Daerobi; Bhimo Rizky Samudro (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2017)
This study aimed to find out the patterns of institutional environments, institutional arrangement, institutional strategies, and policies on community-based water management in rural communities. This research object was Village Water Company (PAMDes) Sumber Agung located in Jalakan Hamlet, Triharjo Village, Pandak Sub-District, Bantul Regency, Special Region of Yogyakarta. Data collection was performed by using an interview to informant or reliable sources. By using Institutional Analysis and Development (IAD), data analysis technique was performed by analyzing the performance and structure of institutional arrangement. Participatory Rural Appraisal (PRA) was used to find out the process of empowerment and enhancement of community participation on community involvement of overall development activities.The results indicated that the Jalakan community had a close relationship with the unwritten rules regarding the applicable rules, such as the merti sendang (clean the pool, embung, springs) or padusan (bathing before the coming of Ramadan).Keywords: Institution, Rural Community, Community Water Management, PAMDes